Long-lived and disorder-free charge transfer states enable endothermic charge separation in efficient non-fullerene organic solar cells - Ture F. Hinrichsen (Nature Portfolio, 2020)
Designing efficient organic solar cells is limited by the energy required to overcome the mutual Coulomb attraction between electron and hole. Here, the authors reveal long-lived and disorder-free charge-transfer states enable efficient endothermic charge separation in non-fullerene systems with marginal energy offset.